POLITIK HUKUM PENGEMBALIAN KETETAPAN MAJELIS PERMUSYAWARATAN RAKYAT DALAM HIRARKI PERATURAN PERUNDANG-UNDANGAN BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2011 TENTANG PERATURAN PERUNDANG-UNDAGAN DI INDONESIA - Jendri Heri Sumarta; Dodi Haryono; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The structure of a legal state in principle is a way to create a complex legal system, to realize the legal order that governs the relationship between the communities by the state or state institutions in a region or country. Hans Kelsen in his book entitled